The Great Bug Hunt - Dobkin, Bonnie; Dunnington, Tom (New York : Childrens Press, 1993)
Children set out looking for insects and they find all kinds.
Appraisal-Science Books for Young People.
Appraisal-Science Books for Young People, November 2005.
1.5.
1.6
K-3
P-2.
Keywords: Insects -- Fiction; Stories in rhyme; Insects -- Fiction; Stories in rhyme; Readers (Elementary).